2001
DOI: 10.1053/euhj.2001.2293
|View full text |Cite
|
Sign up to set email alerts
|

Atrial septal aneurysm as a cardioembolic source in adult patients with stroke and normal carotid arteries. A multicentre study

Abstract: The prevalence of atrial septal aneurysm in patients with cerebral ischaemia and normal carotid arteries was 27.7%, higher than the control group. Atrial septal aneurysm was frequently associated with patent foramen ovale. In patients less than 45 years old, atrial septal aneurysm was the only potential cardiac source of embolism detected with transoesophageal echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 23 publications
2
64
1
11
Order By: Relevance
“…10 Numerous studies have established that there is an increased prevalence of PFO and ASA in patients who have had a cryptogenic stroke. [11][12][13][14][15][16] A comprehensive meta-analysis of casecontrol studies comparing patients under 55 years of age who had an ischemic stroke to control groups of non-stroke patients reported an increased likelihood of finding a PFO (OR ϭ 3.1; 95% CI, 2.3 to 4.2) or an ASA (OR ϭ 6.1; 95% CI, 2.5 to 15.2) in stroke patients. 17 Moreover, multiple studies have shown an association between degree of shunt or size of PFO and the risk of stroke and stroke recurrence.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
“…10 Numerous studies have established that there is an increased prevalence of PFO and ASA in patients who have had a cryptogenic stroke. [11][12][13][14][15][16] A comprehensive meta-analysis of casecontrol studies comparing patients under 55 years of age who had an ischemic stroke to control groups of non-stroke patients reported an increased likelihood of finding a PFO (OR ϭ 3.1; 95% CI, 2.3 to 4.2) or an ASA (OR ϭ 6.1; 95% CI, 2.5 to 15.2) in stroke patients. 17 Moreover, multiple studies have shown an association between degree of shunt or size of PFO and the risk of stroke and stroke recurrence.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
“…The frequency of ASA is higher in patients evaluated with TOE after a cerebral ischaemic event than in the general population. 11 Since ASA is frequently associated with right-to-left interatrial shunting and often associated with large PFOs, it is reported that the mechanism of cardio-embolism is most likely paradoxical embolisation through a coexistent PFO. 12 In our patient two clinical features increased our suspicion of a paradoxical coronary embolus.…”
Section: Discussionmentioning
confidence: 99%
“…Практически у всех больных наблюдается поражение крупных сосудов и сердца. Особое диагностическое значение имеет расшире-ние или аневризма аорты [63]. Типичны нарушения органов зрения: миопия высокой степени, подвы-вих, сферичность, уменьшение размеров хрустали-ка, отслойка сетчатки.…”
Section: синдром марфанаunclassified